A case study of phytoplankton used as a biological index for water quality assessment of Nhu Y river, Thua Thien - Hue - Thi Trang Le,; Quang Doc Luong,; Thi Thu Ha Vo,; Van Tu Nguyen, (Vietnam Journal of Science, Technology and Engineering, 2018)
Studies of the composition and density of phytoplankton and the water quality of Nhu Y river were conducted over six months (March to August 2011). Phytoplankton samples were collected by filtration and immediately preserved in Lugol’s solution. The phytoplankton species composition recorded 117 species belonging to six divisions: Cyanobacteria (24 taxa), Bacillariophyta (14 taxa), Chlorophyta (45 taxa), Euglenophyta (31 taxa), Cryptophyta (2 taxa), and Dinophyta (1 taxa), of which Chlorophyta and Euglenophyta were dominant in terms of species numbers. The total phytoplankton density fluctuated from 110,146 to 5,964x103 individuals/litre and Cyanophyta were dominant in terms of individual density. The algal genus pollution index (Palmer index) ranged from 30 to 41, indicating that the water was highly organically polluted, and the Shannon-Weiner index results of 0.66-2.92 showed moderately to heavily polluted water. With values for the Diatomeae index of more than 0.2, the quality of the eight sites during the period of the study showed that the aquatic environment was eutrophic. Phytoplankton and their indexes are useful tools for assessing water environment quality.